THE ROLE OF INDIGENOUS COMMUNITIES IN SUSTAINABLE TOURISM IN WAKATOBI: A GOOD GOVERNANCE PERSPECTIVE - Mahrudin Udin; Purwanto; Retno Sunu Astuti; Ida Hayu Dwimawanti (CV. RADJA PUBLIKA, 2025)
Wakatobi, located in Southeast Sulawesi, Indonesia, is recognized as one of the country’s leading marine tourism destinations and designated as a UNESCO Biosphere Reserve. However, the sustainability of tourism development in this region relies not only on ecological potential but also on the role of indigenous communities in governance practices. This article examines the role of indigenous communities in sustainable tourism governance in Wakatobi through the lens of good governance. Data were collected using a qualitative approach, including semi-structured interviews with customary leaders, village officials, tourism actors, and domestic and international tourists. The findings demonstrate that indigenous communities play a pivotal role in ensuring transparency through customary marine regulations, fostering participation via homestays and cultural festivals, strengthening accountability in community-based tourism funds, enhancing effectiveness through the integration of customary and formal rules, and promoting equity in the distribution of economic benefits. This study contributes to the literature on sustainable tourism governance by highlighting the centrality of indigenous knowledge in achieving inclusive and sustainable outcomes.